2015
DOI: 10.1002/pssb.201451657
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance and electrical resistivity of N‐doped multi‐walled carbon nanotubes at low temperatures

Abstract: The magnetoresistance and electrical resistivity of nitrogen‐doped multi‐walled carbon nanotubes (N‐MWCNTs) were studied in the temperature range of 1.6–100.3 and 1.6–286 K, respectively, using a standard four‐probe technique. The possible mechanisms of the observed effects are discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
(38 reference statements)
1
5
1
1
Order By: Relevance
“…Thus, according to our research the functionalization of carbon nanotube with the proposed method results in a slight decrease in the value of the Fermi level energy. This result differs significantly for instance from previously published results . It has been shown that the doping of carbon nanotube with nitrogen causing a significant increase (almost 10 times) the value of the Fermi energy level.…”
Section: Resultscontrasting
confidence: 96%
See 1 more Smart Citation
“…Thus, according to our research the functionalization of carbon nanotube with the proposed method results in a slight decrease in the value of the Fermi level energy. This result differs significantly for instance from previously published results . It has been shown that the doping of carbon nanotube with nitrogen causing a significant increase (almost 10 times) the value of the Fermi energy level.…”
Section: Resultscontrasting
confidence: 96%
“…The properties of the carbon nanotubes, associated with charge transfer, were investigated, their kinetic properties can be described in the model of two‐dimensional conduction . For such weakly ordered systems, which are multiwall carbon nanotube at low temperatures, there are quantum effects of weak localization and interaction of charge carriers . One of the characteristic features of these effects is negative magnetoresistance, the absolute value of which increases with decreasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Розрахунки геометричної оптимізації проведено із використанням теорії функціоналу густини. Бор та азот, як домішки, було вибрано з урахуванням літературних даних, де показано, що ці домішки підсилюють адсорбційні властивості вуглецевих наноструктур щодо деяких видів молекул [25][26][27].…”
Section: вступunclassified
“…Together with undoped carbon materials, the B- or N-doped CNTs and graphene were considered in calculations. Such kind of doping can substantially change the physical properties of carbon nanostructures (see e.g., [1517]). As it was found for several kinds of molecules, the doping with nonisovalent impurities B or N can enhance adsorption capabilities of carbon nanostructures [1820].…”
Section: Introductionmentioning
confidence: 99%